Meža jāņeglītes pirmais atradums Latvijā - Jamonte, Daiga (My University, 2021)
Raksts veltīts Latvijā reti sastapta auga meža jāņeglītes Pedicularis sylvatica atradumiem Latvijas teritorījā, izceļot tās pirmo atradumu, ko 1923. gadā veica latviešu botāniķis Pauls Galenieks (1891 - 1962). Rakstā sniegta informācija par meža jāņeglītes herbārijiem Latvijas Universitātes muzejā.

The article is devoted to the finds of wood lousewort Pedicularis sylvatica, a rare plant in Latvia, in the territory of Latvia, highlighting its first finding made in 1923 by the Latvian botanist Pauls Galenieks (1891 - 1962). The article provides information about wood lousewort herbariums in the Museum of the University of Latvia.
First find of wood lousewort in Latvia
Keywords: Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology::Plant physiology; Pedicularis sylvatica L.; meža jāņeglīte; wood lousewort; botany; Rucava; Paul Lackschewitz; Pauls Lakševics; Herbarium Latvicum (RIG II); Herbarium Balticum (RIG I); Herbarium Lackschewitzi (RIG III); herbārijs